2007
DOI: 10.1093/intqhc/mzm052
|View full text |Cite
|
Sign up to set email alerts
|

Differentials in the quality of antenatal care in India

Abstract: Poor quality of antenatal care is likely to reduce its utilization. Policy and program interventions to improve the quality of care of antenatal care, especially for the poor and other disadvantaged population groups, more so in north India, are essential to improve maternal health outcomes. The India's National Rural Health Mission (NRHM), launched in 2005, should lay greater emphasis on improving the quality of antenatal care, among other things, to increase utilization of antenatal care and achieve better m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
97
1
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(108 citation statements)
references
References 16 publications
7
97
1
3
Order By: Relevance
“…71 Another important data gap involves indicators for coverage of stillbirth interventions that should be provided during antenatal or intrapartum care. Many of the interventions to reduce stillbirths, such as appropriate management of hypertensive disease in pregnancy, syphilis screening and treatment, 93,94 or fetal heart rate monitoring, as discussed in the third paper of this Series, 20 are not routinely tracked at the population level. For women who receive care, there are often missed opportunities between the contact point (antenatal or intrapartum) and the provision of high-impact, evidencebased interventions.…”
Section: Comparable Definitionmentioning
confidence: 99%
“…71 Another important data gap involves indicators for coverage of stillbirth interventions that should be provided during antenatal or intrapartum care. Many of the interventions to reduce stillbirths, such as appropriate management of hypertensive disease in pregnancy, syphilis screening and treatment, 93,94 or fetal heart rate monitoring, as discussed in the third paper of this Series, 20 are not routinely tracked at the population level. For women who receive care, there are often missed opportunities between the contact point (antenatal or intrapartum) and the provision of high-impact, evidencebased interventions.…”
Section: Comparable Definitionmentioning
confidence: 99%
“…(Paramedic PACPs are mostly male, whom women are unlikely to visit for antenatal care in this setting because of the gender barrier.) A more recent study also reported the poor quality of antenatal care in the north Indian states and the negative influence this could have on the uptake of such care (Rani et al 2008). The same is the case with skilled attendance at delivery.…”
Section: Discussionmentioning
confidence: 98%
“…These findings were consistent with findings of other studies. [5][6][7][8][9] This study shows that 30.50% babies of unbooked mothers and 19.50% babies of booked mother had Apgar score <7 at one minute (p<0.002) while 12% babies of unbooked mothers and 5.50% babies of booked mothers had Apgar score of <7 at five minute. It indicates that as compared to booked mothers, babies of unbooked mothers were 1.5 times more likely to have birth asphyxia (p<0.002).…”
Section: Discussionmentioning
confidence: 99%